2023
DOI: 10.3390/nano13233006
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Flame Spray Pyrolysis (FSP) Technologies for Engineering Multifunctional Nanostructures and Nanodevices

Christos Dimitriou,
Pavlos Psathas,
Maria Solakidou
et al.

Abstract: Flame spray pyrolysis (FSP) is an industrially scalable technology that enables the engineering of a wide range of metal-based nanomaterials with tailored properties nanoparticles. In the present review, we discuss the recent state-of-the-art advances in FSP technology with regard to nanostructure engineering as well as the FSP reactor setup designs. The challenges of in situ incorporation of nanoparticles into complex functional arrays are reviewed, underscoring FSP’s transformative potential in next-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 245 publications
(470 reference statements)
0
6
0
Order By: Relevance
“…, CO, NO x , NH 3 , acetone, ethanol) with enhanced selectivity and sensitivity, 68,157 and biosensing, where the high surface-to-volume ratio of the nanoparticles enables the effective capturing and signaling of biomolecules. 158 Compared to other methods, FSP is less time-consuming, rapid one-step fabrication, and can be utilized to produce nanoparticles with limited aggregation and a narrow size distribution, which in turn, ensures consistent and reliable sensing performance across various applications. The potent combination of adaptability, efficient synthesis, high purity of nanomaterials, cost effectiveness, and improved sensing capabilities solidifies FSP as a preferred choice in nanoparticle fabrication for chemical sensing technologies.…”
Section: Sensing Applications Of Flame-synthesized Nanostructuresmentioning
confidence: 99%
“…, CO, NO x , NH 3 , acetone, ethanol) with enhanced selectivity and sensitivity, 68,157 and biosensing, where the high surface-to-volume ratio of the nanoparticles enables the effective capturing and signaling of biomolecules. 158 Compared to other methods, FSP is less time-consuming, rapid one-step fabrication, and can be utilized to produce nanoparticles with limited aggregation and a narrow size distribution, which in turn, ensures consistent and reliable sensing performance across various applications. The potent combination of adaptability, efficient synthesis, high purity of nanomaterials, cost effectiveness, and improved sensing capabilities solidifies FSP as a preferred choice in nanoparticle fabrication for chemical sensing technologies.…”
Section: Sensing Applications Of Flame-synthesized Nanostructuresmentioning
confidence: 99%
“…To date, FSP has been extensively utilized in the production of most known metal oxides. 36,37 42,43 NaTaO 3 /NiO, 44 and PdO/Pd 0 /TiO 2 45 have been produced in one step. In the case of RuO 2 , due to the high volatility of Ru-atoms at elevated temperatures (T > 800 °C), such as those occurring in a typical FSP flame, 35 the formation of highly volatile oxides RuO 3 and RuO 4 rather than RuO 2 could be favored.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, flame spray pyrolysis (FSP) is a versatile technology for the engineering of multifunctional nanostructures and nanodevices [ 20 ] with controllable characteristics (size, phase, crystallinity), and can provide nanoparticles at large quantities. Recently, we have demonstrated that FSP can be successfully employed to synthesize highly-photoactive perovskite materials, e.g., BiFeO 3 [ 21 ], NaTaO 3 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the specific aims of the present works were: (i) to develop FSP protocols for controlled Vo-engineering in nanosized SrTiO 3-x , employing an advanced FSP approach in which the combustion stoichiometry was controlled by the FSP-design and operating conditions [ 16 , 20 , 26 , 27 ]; (ii) to study the structural and spectroscopic properties of the so-produced SrTiO 3-x ; (iii) to extend and highlight the versatility of A-FSP as a technique capable of producing large quantities of elaborated nanostructures.…”
Section: Introductionmentioning
confidence: 99%